1977
DOI: 10.1007/bf00441934
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic disorder similar to Zellweger syndrome with hepatic acatalasia and absence of peroxisomes, altered content and redox state of cytochromes, and infantile cirrhosis with hemosiderosis

Abstract: A patient with a cerebro-hepato-renal syndrome was investigated. The visceral manifestations were those of the Zellweger syndrome (ZS); however, the child exhibited muscular hypertonia and survived into the 2nd year of life. Ultramicroscopically, hepatocytes were lacking peroxisomes, but, contrary to findings in one patient with ZS [2], contained smooth endoplasmic reticulum. No catalase was found by histochemistry or spectroscopy. Mitochondria showed normal succinate and glutamate respiration, and normal coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(21 citation statements)
references
References 46 publications
3
18
0
Order By: Relevance
“…We favor this hypothesis because I) long chain fatty acids are known to be oxidized in peroxisomes (14); 2) we presented evidence that the oxidation of C24:O in rat liver takes place in peroxisomes (1 3); 3) we recently showed that patients with the Zellweger cerebrohepatorenal syndrome have elevated levels of very long chain fatty acid levels (3) and impaired I4CO2 production from [l-I4C] C24:O (Singh, I. unpublished observation) similar to observations in ALD; and 4) patients with the Zellweger syndrome lack peroxisomes (6,29,39). Definition of the metabolic defect in ALD will require study of specified subcellular fractions, and analysis of the separate steps involved in fatty acid degradation.…”
Section: Resultsmentioning
confidence: 86%
“…We favor this hypothesis because I) long chain fatty acids are known to be oxidized in peroxisomes (14); 2) we presented evidence that the oxidation of C24:O in rat liver takes place in peroxisomes (1 3); 3) we recently showed that patients with the Zellweger cerebrohepatorenal syndrome have elevated levels of very long chain fatty acid levels (3) and impaired I4CO2 production from [l-I4C] C24:O (Singh, I. unpublished observation) similar to observations in ALD; and 4) patients with the Zellweger syndrome lack peroxisomes (6,29,39). Definition of the metabolic defect in ALD will require study of specified subcellular fractions, and analysis of the separate steps involved in fatty acid degradation.…”
Section: Resultsmentioning
confidence: 86%
“…Furthermore, we propose that the same damage has occurred at the interaction site of NADH dehydrogenase with ubiquinone. The abnormally high oxidation state of cytochrome b in the controlled state, as found by Versmold et al (15), might be a secondary consequence of the proposed damage of succinate-Q-oxidoreductase.…”
Section: [14c02]production Rate From [I-14c]-pymvate [U-14c]-malatmentioning
confidence: 75%
“…The findings of a normal cytochrome content in heart muscle mitochrondria as well as in liver mitochondria are in accordance with the suggestion that the defect is located before the oxidative step involving the cytochromes (4). Versmold et al (15) found a decreased cytochrome content (aas, b, and c) in liver mitochondria from a Zellweger-like syndrome patient'who also showed a deficiency of ~eroxisomes in he~atocvtes. The authors concluded that the de-…”
Section: Methodsmentioning
confidence: 98%
“…DiMauro et al (1980) described deficiencies of cytochrome oxidase in both skeletal muscle and kidney associated with hypercalcaemia, lactic acidaemia and a generalized aminoaciduria. Deficiences of cytochrome oxidase have also been reported in the cerebro-hepato-renal syndrome (Versmold et al, 1977).…”
mentioning
confidence: 95%